EVOLUTION OF PRODUCT PHASE ASSEMBLAGES DURING THERMAL DECOMPOSITION OF MUSCOVITE UNDER STRONG DISEQUILIBRIUM CONDITIONS - Devineau K.; Villieras F.; Devouard B.; Faure F.; Devidal J.-L.; Kohler A. (My University, 2006)
We investigated the thermal decomposition of muscovite in natural granite powders heated to 1175 °C for durations from 5 min to 69 h, at 1 bar, paying special attention to the early stages of decomposition. This study shows that muscovite is completely transformed after 5 min. Muscovite pseudomorphs consist of glass, mullite, and Al-rich oxides. For short durations (5 and 40 min), the Al-rich phase was identified by XRD, electron diffraction, and TEM microanalysis as γ-Al2O3 containing 4-8 wt% FeO (total Fe), probably a few weight percents of MgO, and possibly up to 10 wt% SiO2. Faint superstructure spots and diffuse streaks observed in electron-diffraction patterns suggest vacancy or trace elements ordering in the γ-Al2O3 defect spinel structure. γ-Al2O3 displays an unexpected acicular morphology, elongated along three directions at 120° in the basal (001)musc planes and parallel to lateral faces of the former muscovite. Mullite forms rods elongated in the basal (001)mucs planes along a direction at 90° from one set of γ-Al2O3 needles. The γ-Al2O3 structure appears to be a metastable phase that is replaced by corundum for longer durations.
Keywords: AL-RICH OXIDE; CRYSTAL GROWTH; ELECTRON DIFFRACTION; ELECTRON MICROSCOPY; EXPERIMENTAL PETROLOGY; GRANITE; HIGH-TEMPERATURE STUDIES; MULLITE; MUSCOVITE